CODE-SWITCHING AS MEDIA SPEECH: AN EVIDENCE IN INDONESIAN PODCAST - Fathia Anggriani Pradina (Haluan Sastra Budaya, 2021)
A communicative code plays a main role in every conversation. The aim is to make a communicative goal in every situation. In this digital era, people tend to make something interesting to attract people’s attention. Namely Podcast, is one of the programs in digital platform that been used as the media to share everything in audio output. In Podcast, the host uses code-switching to make the communication livelier and sometimes to emphasize the statements or questions. Therefore, the host and the guest will have a very communicative interaction along the interview. This study aims to analysed the situational goal in a Podcast which host uses English as his switching code. The situational goal can be seen from the type of code-switching that the host used connected to the type of illocutionary forces at the speech act level.  The data are recorded and transcribed from several episodes of the Podcast. The result shows that code-switching as the media speech is deliberately use as a very functional code to reach the situational goal.